Selling Gasoline as a By-Product: The Impact of Market Structure on Local Prices - Justus Haucap; Ulrich Heimeshoff; Manuel Siekmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We use a novel data set with exact price quotes from virtually all German gasoline stations to empirically investigate how a temporary variance in local market structure induced by restricted opening hours of specific players affects price competition. We find that, during their hours of opening, they have a significant negative price effect on nearby competitors.
Keywords: L71; 330